VARIANCE ANALYSIS : EARNED VALUE MANAGEMENT (EVM) - Hutagaol, Kerlima; Prajoko, Alip; Dasrah, Irvon; Prayogo, Muhammad Fairuz Suryo; Putrafakhmi, Dizzy (SINERGI : Jurnal Riset Ilmiah, 2025)
Construction project management is a complex process that involves the integrated management of time, cost, and quality to achieve the desired results as planned. Effective supervision is needed so that the project can run according to the target without experiencing time or cost losses. One method that can be used for project supervision is Earned Value Management (EVM). EVM is a method used to measure project performance by comparing work plans, completed work, and actual costs. This method aims to accurately measure project progress, identify deviations in schedule and cost, and provide guidance in decision making. This research focuses on the application of the EVM method to the Batu Ampar - Sp.3 Muara Wahau Road Preservation Works construction project in East Kalimantan Regency. This road section is a strategic route connecting Samarinda City in East Kalimantan with Tanjung Selor City in North Kalimantan. In this project, handling landslide points is a priority, one of which is the Bore Pile and Foam Mortar work method. The results of this study are expected to provide a real picture of the application of EVM in managing construction project performance and improving the efficiency of time and cost management.